2007
DOI: 10.1111/j.1742-4658.2007.05784.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural characterization of mammalian‐like purine nucleoside phosphorylase from the Archaeon Pyrococcus furiosus

Abstract: Purine nucleoside phosphorylase (PNP) catalyzes the reversible phosphorolytic cleavage of the glycosidic bond of purine nucleosides to produce ribose-1-phosphate and a free purine base [1][2][3]. PNPs have been characterized in a variety of species and may be grouped into two main groups, PNP-1 and PNP-2. PNP-1 are found in prokaryotes, are homohexamers with a subunit of 26 kDa and recognize both 6-oxo and 6-amino purine nucleosides as substrates. PNP-2 are homotrimers, with a subunit molecular mass of We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Guanosine is a natural substrate of hPNP (21). The wild-type enzyme catalyzes the reversible phosphorolysis of guanosine to guanine and ribose-1-phosphate with high efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanosine is a natural substrate of hPNP (21). The wild-type enzyme catalyzes the reversible phosphorolysis of guanosine to guanine and ribose-1-phosphate with high efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures of hPNP in complex with either guanosine or inosine indicate that the N1-C2 side of these nucleotides faces Glu201 of hPNP (8, 16, 22). In fact, the carboxyl side chain of Glu201 forms hydrogen bonds with the amino group at C2 in guanosine and with the N1-hydrogen of both guanosine and inosine (16, 18, 21). Since the prodrugs contain highly electronegative fluorine or chlorine at the C2 position, replacing Glu201 with glutamine should allow the amide group in Gln to form hydrogen bonds with the C2-fluorine (or C2-Chlorine) and N1 of the prodrugs, which may enable the enzyme to accept the prodrugs with higher efficiency (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the samples were treated with 20 percent ␤-mercaptoethanol and boiled for 20 min (conditions that would normally break protein complexes into their corresponding monomers), the appearance of multimeric forms was a surprise. However, it is often observed that multimeric protein complexes from hyperthermophilic organisms such as M. jannaschii persist under SDS-PAGE analysis in even the harshest of conditions (6).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, in intracellular proteins from well‐known organisms, and as a result of the reductive chemical environment inside the cells [3], the presence of these covalent links is limited to proteins involved in the mechanism of the response to redox stress [4] or to proteins catalyzing oxidation–reduction processes [1,5]. Despite this classical view, recent computational, structural and biochemical studies have highlighted the critical role of these covalent links in the structural stabilization of intracellular proteins in some hyperthermophilic Archaea and Bacteria [6–12].…”
Section: Introductionmentioning
confidence: 99%
“…PfPNP displays a much higher similarity with MTAP than with PNP family members [12]. Similar to human PNP [18], PfPNP shows an absolute specificity for inosine and guanosine [12]. SsMTAPII and PfPNP show features of exceptional thermophilicity and thermostability and are characterized by stabilizing disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%